PERANAN PEMERINTAH DALAM PEMBINAAN PEDAGANG KAKI LIMA DI PANTAI LOSARI KOTA MAKASSAR - Abdul Rachim Rauf (AkMen JURNAL ILMIAH, 2011)
Increased street vendors in urban areas provide two influences are positive and negative influences. Positive influence that this business can meet the needs of street vendors, can provide jobs, to contribute to local revenues through sales tax. Generated negative influences is the location occupied by irregular so as to disturb public order such as in doorways, sidewalks, street corners persimpanagn, as well as in various places of the city which is considered good to do business so that the bustle of the city atmosphere, the beauty of the city becomes blurred, obstructed traffic flow and sometimes crime increases, the more dense settlements, as well as hygiene and health is not maintained. Losari local elections are the object of research is based on the consideration that the street vendors in Losari different from street vendors in other public places. Here does not happen destruction and persecution from the government because it is closely associated with the development of Makassar as a Metropolitan City. Therefore, the government issued Decree No. 3479 Mayor Ujung Pandang 1992 on Appointment and Five Foot Settings on The Merchants Throughout Losari.